Analisis Pola Aliran Air Tanah Di Sekitar Saluran Pembuang Pada Lahan Gambut Tropis Dengan Fungsi Lahan Pertanian - Yusup Arianto; Haiki Mart Yupi; Raden Haryo Saputra (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
This study aims to analyze the pattern of groundwater flow around drains on tropical peatlands and to determine the effect of groundwater around drains on tropical peatlands with agricultural land functions. The research data used is primary data, namely water level, distance of each well pipe, coordinate points. In carrying out the analysis process using surfer software.The results showed that the pattern of groundwater flow around the drainage canal on tropical peatlands is that it tends to flow from the land to the drainage canal with the condition that the water level in the channel is lower than the groundwater level on the land.Besides that, from the results of the analysis carried out, it was found that the water level in the drain has an effect on the pattern of groundwater flow in tropical peatlands (agricultural land functions). The greater the difference in the height of the water level in the drainage canal (low water level condition), with the ground water level in the field (high water level condition), the pattern of groundwater flow tends to move towards the canal. However, when the water level in the channel is almost the same as the groundwater level in the field, the pattern of groundwater flow will change.